The influence of the recent financial crisis on the financial situation of Polish listed companies - Jerzy Róçzański; Paweł Kopczyński (e-Finanse: Financial Internet Quarterly, 2017)
The recent financial crisis that began in 2007, also known as the Global Financial Crisis, had a huge influence on the financial situations of enterprises and financial institutions around the world. The situation on world stock markets was also strongly affected by the crisis. As the behavior of investors may be affected by various factors which can impact their decisions on the stock exchanges, some of them may be unable to act in a rational manner and make the right decisions. The huge drop in share prices on world stock markets was visible in the early stages of the crisis. The share price does not always reflect the real situation of the company. The main purpose of this article is to evaluate the influence of the recent financial crisis on the financial situation and performance of Polish listed companies. Financial ratios will be utilized to evaluate the real changes in the financial situation of Polish listed companies during the crisis. A large group of companies will be covered by the survey in order to assess the impact of macroeconomic factors on the financial situations of enterprises in different phases of the crisis. Market tests will not be applied because they may be affected by changes in share prices which in turn are often affected by irrational decision-making and fear.
Keywords: G1; G2; G3; 330; financial statement analysis; financial situation and performance of listed companies; global financial crisis; financial ratios